PRODUCT QUALITY MANAGEMENT WITH THE USE OF MANAGEMENT INFORMATION SYSTEMS AS THE BASIS OF DIGITAL COMPETITIVENESS OF BUSINESS IN THE AI ECONOMY - Aziza B. Karbekova; Gulmira A. Abdrazakova; Tamara A. Ergeshova; Alexey V. Tolmachev; Meri V. Badalyan (Proceedings on Engineering Sciences)
We analysed the directions of quality management in the conditions of using intellectual management information systems, which are most widespread in countries that are leaders in digital competitiveness. We revealed a connection between the level of development of the IT sector, the intensity of development of high technologies, and the level of countries' digital competitiveness. More opportunities for achieving the indicators of product quality are observed with companies that work in countries with a high level of technology transfer. The creation of its national technological basis facilitates an increase in technological indicators of product quality and its integration into international markets. We analysed countries with a high level of digital competitiveness and revealed models of intellectual management of product quality that are peculiar to their practice. The goal of this research was to elaborate on the directions of product quality management with the use of management information systems which ensure digital competitiveness of business in the AI economy. The novel aspect of this paper lies in the determination of the specifics of the formation of digital competitiveness in countries that are leaders in the AI economy.